Pasar Ekologis Sebagai Arah Pengembangan Tata Kelola Kelembagaan Badan Usaha Milik Desa Mardi Gemi di Desa Gari Gunungkidul - Octastefani, Theresia; Prabaningrum, Galih; Mutia Sadasri, Lidwina (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2018)
This research focuses on how to develop the institutional governance in Village-Owned Enterprises(known as BUM Desa)Mardi Gemi with one of its business units is Argo Wijil Ecological Market. The establishment of this ecological market is initiated by the Ministry of Environment and Forestry (KLHK) through the Directorate General of Pollution Control and Environmental Degradation (DG PPKL) to restore the location of former illegal limestone mines and minimize the natural disasters risk that may result from environmental damage. In doing this research, we used qualitative research methods and for collecting data, we used in-depth interviews, observations, and literature study. The results of this study showed that in developing of institutional governance, the Government of Gari Village, the Manager of BUM DesaMardi Gemi, and market traders need to synergize further to formulate Market Standard Operational Procedures (SOP)to serve as guidelines for implementation this ecological market. This market also can realize the practice to create a friendly environment market atmosphere, moreover, it can be used to empower the community as well as to improve the community welfare. So, Argo Wijil Ecological Market can have a multiplier effect for all Gari Village community.Riset ini memfokuskan pada pengembangan tata kelola kelembagaan Badan Usaha Milik Desa (BUM Desa)Mardi Gemi dengan salah satu unit usahanya yaituPasar Ekologis Argo Wijil. Pembentukan pasar ekologis ini diinisiasi oleh Kementerian Lingkungan Hidup dan Kehutanan (KLHK) melalui Direktorat Jenderal Pengendalian Pencemaran dan Kerusakan Lingkungan (Ditjen PPKL) untuk memulihkan lokasi bekas tambang illegal batukapur (gamping)milik rakyat dan meminimalisir risiko bencana alam yang mungkin terjadi akibat kerusakan lingkungan. Untuk itu, dalam kajian ini penulismenggunakan metode penelitian kualitatif dengan penggumpulan data melalui wawancara mendalam, observasi, danstudi literatur.Hasil dari kajian ini menunjukkan bahwa dalam pengembangan tata kelola kelembagaan, Pemerintah Desa Gari, Pengelola BUM Desa, dan pedagang pasar perlu bersinergi lebih lanjut untuk merumuskan Standar Operasional Prosedur (SOP)Pasar agar menjadi pedoman pelaksanaan. Selain itu, pasar ini dapat merealisasikan praktik pasar dengan suasana yang ramah lingkungan sekaligus menjadi media pemberdayaan masyarakat guna mendorong peningkatan kesejahteraan warga. Dengan demikian, Pasar Ekologis Argo Wijil dapat memberikan multiplier effectbagi seluruh masyarakat Desa Gari.